PENGARUH KOMPOS DARI LIMBAH LUMPUR IPAL INDUSTRI KERTAS TERHADAP TANAMAN DAN AIR PERKOLAT TANAH - Rina S. Soetopo; Sri Purwati (Center for Pulp and Paper, 2006)
The influence of the sludge waste compost of paper mill wastewater treatment plant (WWTP) to vegetation and soil percolate water has been investigated. Composting process was done for 45 days by using sawdust as mixed material in the amount of 20% v/v. Compost affect was done to corn vegetation with some dose variation, and manure from chicken with the same dose was also done for the comparator. To know the possibilities of the compost substances wash out into soil and carry over into subsoil water, it was done by using two lysimeter apparatus. The first lysimeter was added by compost in the amount of 11.5 ton/ha and the second one was no added compost. Observation of compost effect to vegetation was carried out to corn harvesting result consist of 1000 gram weight of corn, heavy metal content and acute toxicity test. Results reveal that the compost of sludge waste generally contains total heavy metals are below the quality standard of compost according to SNI and some other state (USA, Europe Union and Australian). Compost had tough pH of 6.5-7.5 and had cation exchange capacity of 33.71 meq/100 g. The compost effect on dose up to 11.5 ton/ha to 1000 grains corn weight was almost the same by using manure in the same dose. The heavy metals content in the corn grain harvested from the land fertilized by sludge waste compost of 11.5 ton/ha was under the Dirjen POM No 03725/B/SK/VII/89 standard. Acute toxicity test on corn grain show that its concentration is higher than 15,884 mg/kg body weight, and it can be classified as non toxic practically. Inti sari Percobaan pengaruh kompos dari limbah lumpur IPAL industri kertas terhadap tanaman dan air tanah telah dilakukan. Proses pembuatan kompos dilakukan selama 45 hari dengan bahan pencampur serbuk kayu 20%v/v. Percobaan dilakukan terhadap tanaman jagung dengan beberapa variasi dosis dan sebagai pembanding adalah pupuk kandang dari kotoran ayam pada dosis yang sama. Pengaruh kompos terhadap air tanah diamati melalui percobaan dengan menggunakan 2 buah lisimeter. Lisimeter pertama ditambah kompos 11,5 ton/ha dan lisimeter kedua tanpa ditambah kompos sebagai kontrol. Pengamatan pengaruh kompos terhadap tanaman dilakukan terhadap hasil panen jagung, kandungan logam berat dan uji toksisitas akut. Hasil percobaan menunjukkan bahwa kompos dari lumpur IPAL, umumnya mengandung logam berat total yang lebih rendah dari baku mutu kompos menurut SNI dan beberapa negara lain (USA, Uni Eropa dan Australia). Kompos mempunyai pH netral (6,5-7,5) dan nilai KTK 33,71meq/100g. Pengaruh dosis kompos lumpur IPAL sampai 11,5 ton/ha terhadap berat 1000 butir jagung relatif sama dengan yang diberi pupuk kandang pada dosis yang sama. Kandungan logam berat dalam biji jagung yang dipanen dari tanah yang dipupuk kompos lumpur IPAL 11,5 ton/ha lebih rendah dari persyaratan maksimum batasan cemaran logam berat dalam makanan untuk kelompok sayur dan hasil olahannya menurut Dirjen POM No. 03725/B/Sk/Vii/89. Hasil uji toksisitas akut jagung lebih besar dari 15884 mg/kg berat badan dan termasuk klasifikasi praktis tidak toksik.